Investigation of sediment buffering function of the Gatberg Floodplain Wetland in the upper Tsitsa River Catchment, South Africa - Pakati, Sibuyisele Sweetness (Rhodes University, Faculty of Science, Department of Geography)
Floodplain wetlands are important components of river systems that provide various ecosystem services such as sediment buffering. These wide and often expansive storage areas have a substantial impact on downstream water quality by trapping sediment and storing 'contaminants' adhered to sediment thus improving water quality. The planned construction of the Ntabelanga and Lalini Dams in the Tsitsa River Catchment has been proposed; however, due to the steep landscapes and erodible soils, this promotes high erosion rates that can potentially reduce the lifespan of the proposed dams. The existing wetlands in the Tsitsa River Catchment have therefore been identified as key sediment buffers that can reduce sediment transport, but the effectiveness of these buffers is poorly researched. This study attempts to investigate the current sediment buffering function of the Gatberg Floodplain Wetland over one wet season (August 2019 to August 2020). Time integrated samplers were installed above and below the wetland to determine relative sediment volume and character coming in and out of the wetland. Five transects were surveyed across the wetland width to evaluate the topography and vegetation characteristics. Surface sediment samples on the floodplain were taken at key morphological features along each transect and along the river longitudinal profile to determine organic content, particle size, and type of stored sediment. Astro turf mats were deployed on targeted transects and on key floodplain features to determine sediment accumulation rates. Field measurements of vegetation parameters (height, density, and stem diameter) were taken to calculate vegetation-induced hydraulic roughness to understand possible sedimentation feedbacks. The relative sediment volume coming into the wetland was greater than that leaving the wetland. This implies that some of the sediment is buffered within the wetland. An approximate proportion of 73% trapping efficiency of the incoming sediment was buffered within the floodplain wetland during the wet season. This accumulated approximately 4 tons within the wetland over the monitoring frame. Bed particle size in the longitudinal profile increased with distance downstream, this was due to localized tributary and hillslope inputs. Inundation depth varied across the floodplain wetland with deeper inundation depths at the head of the wetland than at the bottom; where particle size was larger with an increase in water level depth. This may be linked to both high stream velocities and variability of the floodplain topography. However, the observed trends were inconclusive and uncertain. Stronger correlations with particle size were shown by vegetation roughness (b* = 0.41) and distance from the channel (b* = -0.38). Flood benches and banks had a coarser D50 particle size than back swamps and oxbows. Coarser sediment in flood benches are associated with proximity to the sediment-laden water that experiences abrupt flow velocity changes, while finer material in oxbows are due to minimal flow velocities which reduce with distance from the channel. Finer particles remain in suspension and are carried aloft for longer periods at very low velocities. Therefore, particle size decreased with distance from the channel due to longer travel distances and high surface area relative to weight. Further results showed that finer surface sediment particle size was associated with high vegetation roughness whilst coarser material was associated with low roughness. This was due to vegetation geometry and type or changes in flow velocity and energy. Grassy vegetation induced finer particle size than shrubby vegetation that has a greater line spacing. Furthermore, vegetation roughness varied over the wet season; roughness was highest in late summer and low in early summer. Low roughness was due to fire occurrence in the study area which resulted in a decrease in biomass. Increasing vegetation roughness can be due to increased flood events, and the introduction of non-perennial species; which can increase sediment accumulation rates. Although studies have shown that vegetation density is the most essential factor affecting flow resistance and sedimentation processes; vegetation height and stem diameter for this study area seem to contrast these observations and rather may be the most significant contributing factors in sedimentation. This concluded that vegetation density may not always be the most essential component in sedimentation processes. Sediment particle size was inversely proportional to organic content; finer particle size are more cohesive and more capable of carrying organics. Regions further away from the channel such as oxbows with stable moisture conditions favour plant growth and soil formation thus are susceptible to high organic content. Flood benches are closer to the channel, thus have coarser material and fluctuating moisture conditions that have unstable high water flow velocities. High sediment accumulation rates on flood benches and oxbows is due to high connectivity to sediment-laden water and high hydroperiods or high residence time for sediment accumulation in oxbows. Sediment accumulation rate was shown to be a function of particle size itself (b* = 0.67) rather than the expected vegetation roughness. Although a true representation of sediment accumulation rates in the Gatberg Wetland was limited by the disturbance of astro turf mats by animals and possibly by high flooding events; the wetland can be regarded as a good sediment buffer as some sediment was stored (e.g. up to 48,04 kg/m2 in flood benches) within the wetland over the monitoring period.
Keywords: Sedimentation and deposition -- South Africa -- Eastern Cape; Sediment transport -- South Africa -- Eastern Cape; Floodplain morphology -- South Africa -- Eastern Cape; Wetlands -- South Africa -- Eastern Cape; Suspended sediments -- South Africa -- Eastern Cape; Floods -- South Africa -- Eastern Cape; Fluvial geomorphology -- South Africa -- Eastern Cape; Floodplain plants -- South Africa -- Eastern Cape; Inundation depth